Digital Twin Technology: Concepts and Applications - Tripathi , Diwakar R.; Nishad, Dipesh Kumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Digital twin technology has emerged as a powerful tool for modeling and simulating complex systems in various industries. This paper provides a comprehensive overview of digital twin technology, including its definition, historical background, key concepts, and components. The paper also explores the different types of digital twins, such as product twins, process twins, system twins, and enterprise twins, and discusses their applications in the manufacturing, healthcare, and smart cities sectors. Furthermore, the paper examines the challenges facing digital twin technology, such as data privacy and security, integration with the Internet of Things (IoT), and the need for enhanced realism and interactivity. The paper concludes by highlighting the potential for artificial intelligence (AI) integration to further enhance the capabilities of digital twin technology and drive innovation in various industries.